Description of a new species of Oplitis Berlese, 1884, and the first record of a phoretic uropodid mite (Acari: Oplitidae) on a Neotropical solitary wasp (Hymenoptera: Vespidae) - Pereira, Matheus Carvalho Soares De Aguiar; Kontschán, Jenő; Bernardi, Leopoldo Ferreira De Oliveira; Hermes, Marcel Gustavo (Zootaxa, 2016)
The association of an uropodid mite with a solitary eumenine wasp is reported for the first time. Five mite specimens were found on a specimen of the wasp Zethus pallidus Smith, 1857, collected in southeastern Brazil. The mites are described as a new species, Oplitis ticumbi Kontschán & Bernardi sp. nov. In addition some notes on the biology of these mite specimens associated with Z. pallidus are presented.